The reliability of the standing long jump in NCAA track and field athletes - Reid, C.; Dolan, M.; DeBeliso, M. (International Journal of Sports Science, 2017)
Many athletes require lower body power for their various sports, such as track and field athletes. When determining this particular attribute in track and field athletes, it is vital that the reliability of the test is determined for the particular athletic group so that coaches can monitor the training state of the athletes. PURPOSE: The purpose of this study was to determine the reliability of the standing long jump (SLJ) in NCAA track and field athletes. METHODS: Thirteen NCAA Division I track and field athletes (male n=6 and female n=7) (age: 21.0±2.0yrs, height: 178.0±7.6cm, mass: 80.0±18.2kg) participated in three trials of the SLJ. After completing a dynamic warm-up, the trials of the SLJ were executed. The athletes stayed warmed-up in between the trials, walking and jogging to keep moving, as is the nature of athletics. In completing the SLJ trials, the athletes performed a standard countermovement SLJ, and distance was measured from the starting line to where the rear heel was upon landing. In order to determine the reliability of the SLJ, the best of Trials 1 and 2, were compared to Trial 3 with: Pearson (PCC) and Intraclass Correlation Coefficients (ICC), SEm, delta Means, and CV%. RESULTS: The best of trial 1 and trial 2 SLJ scores were: 2.37±0.37m, while trial 3 scores were: 2.39±0.37m. The interclass reliability coefficient was r=0.99 (UL:1.00, LL:0.97). The intraclass reliability coefficient was ICC=0.99 (UL:1.00, LL:0.97). The Standard Error of Measurement (SEm) =0.04m (UL:0.07, LL:0.03). The delta Means= 0.02±0.06m (UL:0.05, LL:-0.01). The typical error CV% =1.97 (UL:3.0, LL:1.5). CONCLUSION: Within the parameters of this study, it was found that the SLJ is a highly reliable field test of horizontal muscular power for collegiate track and field athletes.